Faktor Risiko Penyebab Stunting pada Balita Usia 6-36 Bulan: Risk Factors Causing Stunting in Toddlers Aged 6-36 Months - Widyawati, Sigit Ambar; Yuliaji Siswanto; Alfan Afandi (Indonesian Journal of Midwifery (IJM), 2023)
Stunting is a condition of chronic malnutrition that occurs during the critical period of the growth and development process starting from the fetus. Indonesia has quite a serious nutritional problem which is characterized by many cases of malnutrition. Malnutrition is an impact of nutritional status. Stunting or short stature, a condition where a person's height  does not match their age, is determined by calculating the Z-index score for Height according to Age . The type of research chosen was observational analytics with a cross sectional study approach. The population in this study were all mothers who had babies aged 6-36 months in Pabelan District with a sample size of 119 respondents. Data collection was carried out by means of interviews and filling out questionnaires. Data analysis was carried out in stages, starting with univariate analysis, bivariate analysis using the chi-square test, followed by multivariate analysis. The bivariate test results showed that variables related to the incidence of stunting were parenting style (p=0.012), mother's knowledge about nutrition (p=0.066), and mother's knowledge about exclusive breastfeeding (p=0.232). The results of the multivariate logistic regression showed that the parenting pattern variable was (p=0.018) with a strength of relationship of OR 4.029. This shows that respondents who have poor parenting styles have a 4.029 times greater risk of stunting.   Abstrak Stunting adalah suatu kondisi kekurangan gizi kronis yang terjadi pada saat periode kritis dari proses tumbuh dan kembang mulai janin. Indonesia mempunyai masalah gizi yang cukup berat yang ditandai dengan banyaknya kasus gizi kurang. Malnutrisi merupakan suatu dampak keadaan status gizi. Stunting atau perawakan pendek (shortness), suatu keadaan tinggi badan (TB) seseorang yang tidak sesuai dengan umur, yang penentuannya dilakukan dengan menghitung skor Z-indeks Tinggi Badan menurut Umur (TB/U). Jenis penelitian yang dipilih adalah analitik observasional dengan pendekatan studi cross sectional. Populasi dalam penelitian ini adalah seluruh ibu yang memiliki bayi usia 6-36 bulan di Kecamatan Pabelan dengan jumlah sampel sebanyak 119 responden. Pengambilan data dilakukan dengan cara wawancara dan pengisian kuesioner. Analisis data dilakukan secara bertahap, yaitu diawali dengan analisis univariat, bivariat menggunakan uji chi-square dilanjutkan multivariat. Hasil uji bivariat menunjukkan variabel yang berhubungan dengan kejadian stunting yaitu pola asuh (p=0,012), pengetahuan ibu tentang gizi (p=0,066), dan pengetahuan ibu tentang ASI Eksklusif (p=0,232). Hasil regresi logistik multivariat didapatkan variabel pola asuh (p=0,018) dengan kekuatan hubungan sebesar OR 4,029. Hal ini menunjukkan bahwa responden yang memiliki pola asuh kurang memiliki risiko  4,029 kali lebih besar untuk terjadinya stunting.